Economic Implications of Defense Supply Chain Vulnerabilities in Geopolitical Crises - Retno Pratiwi Andari; Djoko Andreas Navalino; Heru Prasetyo (CV. AFDIFAL MAJU BERKAH, 2025)
This research explains the Economic Implications of Defense Supply Chain Vulnerability in Geopolitical Crises by using qualitative methods researchers collect data through triangulation (combined) data collection techniques, inductive data analysis, and qualitative research results emphasize meaning rather than generalization and researchers collect data through a literature study approach by conducting a thorough review of academic articles, websites related to supply chains and those related to defense economics, supply chain management, and geopolitical crises. In an increasingly volatile geopolitical landscape, defense supply chain vulnerabilities have emerged as a critical challenge to national security and economic stability. Geopolitical crises, including the Ukraine-Russia conflict and rising Indo-Pacific tensions, reveal weaknesses such as delays in the delivery of military assets, shortages of advanced technologies and disruptions in the procurement of raw materials. These vulnerabilities lead to increased production costs, inflation and misallocation of resources, affecting not only the defense sector but also the broader economy that relies on interconnected industries. The study underscores the importance of integrating economic policies and defense strategies to improve supply chain resilience, emphasizing lessons from geopolitical crises and the need for international cooperation in securing critical materials.